Biopori dan Keberlanjutan: Mewujudkan Lingkungan yang Lebih Sehat - Siti Aminah; Safira Aluna Rahardani; Dewi Anggraeni; Himmatut Taqiyah; Siti Jamilatul Afifa; Rinna Damayanti; M. Sailful Rizal; M. Aufa Oktavin Ramdani (Yayasan Aya Sophia Indonesia, 2025)
Biopores are a simple technology that functions as water absorption channels and a medium for processing organic waste. This article describes the application of biopores in a community service program in Trebungan Village, Mlandingan District, Situbondo Regency. This paper explains the contribution of biopores to maintaining environmental sustainability, reducing the threat of flooding, and increasing soil fertility. By utilizing biopores, the community can participate in more effective natural resource management and create a cleaner and healthier environment.